2018
DOI: 10.4103/ijmr.ijmr_1844_16
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of obesity & comorbid conditions with chronic venous insufficiency: Results of a single-centre study

Abstract: Background & objectives:Chronic venous insufficiency (CVI) is a common clinical problem among obese patients. This study was conducted to evaluate the impact of body mass index (BMI) and associated morbidities such as diabetes, hypertension and hypothyroidism on venous disease clinical scores as per Clinical, Etiological, Anatomical, Pathological (CEAP) classification.Methods:In this study, adult patients with BMI more than 30 kg/m2 with signs of CVI were evaluated clinically and by using Duplex ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Higher BMI has been associated with less willingness to adhere to general health care requests/recommendations and to wear custom‐made footwear to prevent diabetic ulcers than patients with lower BMIs, and among patients with chronic venous insufficiency, BMI was significantly associated with less compliance with compression therapy . Conversely, as patients with higher BMI are more likely to have preexisting or to develop higher‐grade chronic venous insufficiency, it is possible that higher‐BMI patients in our study were more compliant with ECSs due to greater chronic venous symptom burden.…”
Section: Discussionmentioning
confidence: 99%
“…Higher BMI has been associated with less willingness to adhere to general health care requests/recommendations and to wear custom‐made footwear to prevent diabetic ulcers than patients with lower BMIs, and among patients with chronic venous insufficiency, BMI was significantly associated with less compliance with compression therapy . Conversely, as patients with higher BMI are more likely to have preexisting or to develop higher‐grade chronic venous insufficiency, it is possible that higher‐BMI patients in our study were more compliant with ECSs due to greater chronic venous symptom burden.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complications are superficial thrombophlebitis, acute bleeding originating in one of the thin-walled varices, eczema and skin ulceration. 9 A high BMI is a critical risk factor for CVI. 1 In this study, it was established that a patient with a high BMI (>25kg/m 2 ) had a higher probability of developing CVI in Another study done by Matic et al showed a correlation between patients with a BMI of >30 (kg/m 2 ) and its effects on the development of CVI.…”
Section: Discussionmentioning
confidence: 99%
“…The complex factors that lead to vascular dysfunction in diabetes and peripheral vascular disease can also affect the venous system, resulting in incompetence of the lower extremity venous valves. 47 In fact, prior work from our group has linked venous reflux to peripheral vascular disease, which remains the major cause of lower limb amputation in diabetic patients. 2,19,[48][49][50] In our population, the overall rate of deep vein thrombosis in the lower extremity was 3.8 percent compared to the general inpatient rate of 1 percent.…”
Section: Venous Ultrasoundmentioning
confidence: 99%